AKTUALISASI SISTEM PELEMPAR BOLA PADA ROBOT ISOLA_229 - Nabawi A.M., Ridha; R. Aam Hamdani; Asep Hadian Sasmita (Universitas Nusa Putra, 2020)
The ISOLA_229 robot is designed to have a maximum dimension of a cube of 1 m3 with an extension of up to 1.8m, must be able to throw the ball in 3 throwing zones that have different shooting distances and heights according to the rules of the ABU Robocon robot contest with the theme